CONSTITUTIONAL REVIEW DI INDONESIA PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 48/PUU-IX/2011: DARI NEGATIVE LEGISLATOR MENJADI POSITIVE LEGISLATOR - Xavier Nugraha; Risdiana Izzaty; Alya Anira (RechtIdee, 2020)
The Constitutional Court carrying out its duties regarding the constitutional review acts as a negative legislator which canceling laws that are contrary to the 1945 Constitution. This study examines the political shift of constitutional review law where the Constitutional Court only acts as a negative legislator, but nowadays Constitutional Court acts as a positive legislator. The research method used is normative research. The results of this study conclude that the Constitutional Court Ruling reflects the role of a positive legislator is a progressive and responsive decision to avoid legal chaos due to legal vacuum in society. However, it does not mean that the decision of the Constitutional Court can always be a positive legislator. Only in circumstances based on 3 (three) indicators, namely: a) Justice and benefit of the community; b) An urgent situation; c) Filling out legal vacancies (rechtvacuum) to avoid chaos or legal chaos in the community, then the Constitutional Court Decision can be a positive legislator so that there is still a balance in the check and balances system. Keywords: Constitutional Review, Positive Legislator, Negative Legislator